The Effect of Chicory Consumption on Oxidative Stress Indices of the Kidney Tissue in Female Wistar Rats Consuming Testosterone Enanthate during eight weeks Resistance Training - Khadijeh Molaei; Sanaz Mirzayan Shanjani; Ali Gorzi; Yaser Kazemzadeh; Abdolali Banaeifar (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: Testosterone enanthate is one of the common drugs among female athletes, and one of its basic side effects is the oxidative stress increase. Chicory is considered due to its antioxidant and protective effects. Therefore, the aim of this study was investigating the effect of chicory extract on SOD, GPX and MDA in the kidney tissue of female wistar rats during eight weeks' resistance training. Materials and Methods: 22 female wistar rats aged 8 weeks and weighing 208.22±14.17 grams were provided from Pasteur Institute (Iran). After one week familiarization, the rats were randomly divided into 3 groups, 1) training + placebo group (n=6), 2) training + testosterone enanthate group (n=8), 3) training + testosterone enanthate + chicory group (n=8). Rats carried out eight weeks of resistance training with a 26-step ladder with weights (five days a week). Rats in the testosterone groups received steroid (testosterone enanthate/dose 20 mg) (in the form of injection) and chicory supplement (6 g/kg of body weight) (in the form of gavage) three times a week. Levels of superoxide dismutase (SOD), glutathione peroxidase (GPX) and malondialdehyde (MDA) assessed by spectrophotometric methods, and one-way analysis of variance test was performed to compare intergroup differences along with Bonferroni's post hoc test for pairwise comparison. Results: Consumption of testosterone causes a significant decrease in the level of GPX and SOD factors in rats (P<0.0001) and a significant increase in the level of MDA factor (P<0.0001) compared to the placebo group, and treatment with chicory causes a significant increase in the level The GPX and SOD factors of the rat and the significant decrease of their MDA factor level compared to the placebo rats are in the kidney tissue. Conclusion: Our results indicate that the consumption of testosterone causes a decrease in the activity of antioxidant enzymes and an increase in oxidative stress in the resistance training rats body. Consuming chicory, along with testosterone supplementation, caused the level of these oxidative stress factors to return to their levels in placebo rats.